Hypertension, Dietary Sodium, and Cognitive Decline: Results From the Women’s Health Initiative Memory Study - Haring, Bernhard (Am J Hypertens, 2016)
BACKGROUND: To investigate the relationships of hypertension, antihypertensive treatment, and sodium intake on cognitive decline in older women. METHODS: Prospective follow-up of 6,426 cognitively intact women aged 65–79 years enrolled in the Women’s Health Initiative Memory Study (WHIMS) with a median follow-up of 9.1 years. Dietary sodium intake was determined by food frequency questionnaires. Hypertension was defined as self-report of current drug therapy for hypertension. Blood pressure (BP) control was assessed by treatment for hypertension and clinic measurement of systolic BP ≥ 140mm Hg or diastolic BP ≥ 90mm Hg at baseline. Cognitive functioning was assessed annually by global cognitive screening, neurocognitive, and neuropsychiatric evaluations. Cognitive decline was identified by the incidence of mild cognitive impairment (MCI) or probable dementia (PD). Cox proportional hazards analyses were used to calculate hazard ratios (HRs). RESULTS: Hypertension was associated with an increased risk for cognitive decline (HR 1.20; 95% confidence interval (CI) 1.04, 1.39; P = 0.02). Among women with antihypertensive medication, those with BP ≥140/90mm Hg (uncontrolled BP) were at highest risk for developing cognitive decline (HR 1.30; 95% CI 1.05, 1.60) compared to women without treatment and BP <140/90mm Hg (controlled BP). Sodium intake >1,500mg/day did not alter the risk for cognitive decline in hypertensive women or women with antihypertensive treatment (P (for interaction) = 0.96 or 0.97). CONCLUSIONS: Women with antihypertensive treatment and uncontrolled BP showed highest risk estimates for developing cognitive decline compared to non-hypertensive women. Sodium intake did not modify the risk for cognitive decline in women with hypertension or receiving antihypertensive medication. CLINICAL TRIAL REGISTRATION: http://www.clinicaltrials.gov. Unique identifier: NCT00685009 and NCT00745056